Butterfly Hug To Reduce Academic Stress In Psychology Students - Faizal Kadri; Ahmad Ridfah; Ismalandari Ismail (Polteknik Ilmu Pemasyarakatan, 2023)
Students are a group of individuals who are studying at a university to develop abilities and skills in a field. However, to develop these abilities students must face many demands that must be resolved, and that is what makes students feel pressured and experience academic stress. This study aims to determine the effectiveness of butterfly hug in reducing academic stress in college students. The research participants totaled (N = 11) who were the class of 2021 and 2022 who fell into the high and medium stress categories. Researchers used the experimental design of the one group pretest-posttest design using a double pretest and posttest. the measuring instrument used was the academic stress scale. Scale reliability was measured by calculating the Cronbach Alpha coefficient with a value of 0.847 which indicates high reliability. This study uses the Friedman Test data analysis technique which is processed with SPSS version 24. The results showed that the butterfly hug was effective in reducing academic stress with an Asymp. Sig. of 0.000 <0.05, with a Chi-Square value of 26.063, and Mean Rank O1 of 3.35, O2 of 3.65, O3 of 1.75, and O4 of 1.25. So it can be concluded that there is an effectiveness of butterfly hug in reducing academic stress in students of the Faculty of Psychology, Makassar State University. This research provides an alternative as one of the intervention methods in reducing academic stress in students.